Scenario-Based Evaluation of Perception of Picture Quality Failures in LCD Televisions - Keijzers, J.; Scholten, L.; Lu, Y.; den Ouden, E. (Cranfield University Press, 2009)
In innovative Consumer Electronics products, such as LCD televisions, consumers often perceive the product's malfunctioning differently than designers do. To support critical design decisions, it is therefore important to understand how consumers perceive potential product failures. This paper discusses the development of realistic failure scenarios related to the picture quality of an LCD television. The impact of television content as well as failure origin on the perception of failures is evaluated in an experiment. Advantages and drawbacks of using the scenarios to evaluate design decisions, and implications for further research are discussed.
Organised by: Cranfield University
Keywords: Scenario; Product Design; User-Perceived Failure; Consumer Electronics